2014
DOI: 10.1111/1462-2920.12476
|View full text |Cite
|
Sign up to set email alerts
|

The Campylobacter jejuniRacRS system regulates fumarate utilization in a low oxygen environment

Abstract: The natural environment of the human pathogen Campylobacter jejuni is the gastrointestinal tract of warm-blooded animals. In the gut, the availability of oxygen is limited; therefore, less efficient electron acceptors such as nitrate or fumarate are used by C. jejuni. The molecular mechanisms that regulate the activity of the highly branched respiratory chain of C. jejuni are still a mystery mainly because C. jejuni lacks homologues of transcription factors known to regulate energy metabolism in other bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 65 publications
1
40
0
Order By: Relevance
“…A recent study of the RacRS TCS of C. jejuni revealed that chuC, Cjj0210-Cjj0211, and Cjj1385-Cjj1386 expression levels were all decreased in a racR mutant (27). However, expression of the Cjj1484-Cjj1483 TCS, which is the subject of this work, was significantly higher in the racR mutant (27). Further investigation was unable to demonstrate that RacR interacted specifically with the promoters for chuC, Cjj0210-Cjj0211, and Cjj1385-Cjj1386, creating some speculation about whether the RacRS TCS may only indirectly regulate expression of these genes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study of the RacRS TCS of C. jejuni revealed that chuC, Cjj0210-Cjj0211, and Cjj1385-Cjj1386 expression levels were all decreased in a racR mutant (27). However, expression of the Cjj1484-Cjj1483 TCS, which is the subject of this work, was significantly higher in the racR mutant (27). Further investigation was unable to demonstrate that RacR interacted specifically with the promoters for chuC, Cjj0210-Cjj0211, and Cjj1385-Cjj1386, creating some speculation about whether the RacRS TCS may only indirectly regulate expression of these genes.…”
Section: Discussionmentioning
confidence: 99%
“…For Cjj0210-Cjj0211, chuC, exbB2, and exbD2, evidence exists that the peroxide regulator (PerR) also influences expression of these genes (55). A recent study of the RacRS TCS of C. jejuni revealed that chuC, Cjj0210-Cjj0211, and Cjj1385-Cjj1386 expression levels were all decreased in a racR mutant (27). However, expression of the Cjj1484-Cjj1483 TCS, which is the subject of this work, was significantly higher in the racR mutant (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we were unable to show that acetylphosphate can phosphorylate RacR in in vitro experiments, nor did we observe contrasting phenotypes in pta and ackA mutant strains, which produce low or high levels of acetylphosphate respectively (data not shown). Another possibility is that unphosphorylated RacR has residual transcription inducing activity, as it still binds to its target promotors in the unphosphorylated state in vitro (van der Stel et al, 2015a). The cj1000 mutant strain showed an increase in GGT activity in the exponential growth phase but no change in GOGAT activity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…After 3, 6, 9 or 15 h cultures were harvested and RNA was isolated immediately using the RNA-Bee kit. RT-qPCR was performed as before (van der Stel et al, 2015a). In brief, DNAse treated RNA (10 ng) was used to determine the amount of specific transcripts using the Takyon No Rox qPCR-kit with Euroscript II reverse transcriptase (Eurogentec, Seraing, Belgium), according to the manufacture's protocol in a Lightcycler 480 machine (Roche, Penzberg, Germany) using custom DNA-oligo's (Supporting Information Table S2).…”
Section: Rt-qpcrmentioning
confidence: 99%